Faktor yang Memengaruhi Kepatuhan Imunisasi Tetanus Toksoid Ibu Hamil - Musfirah Musfirah; Muhammad Rifai; Abdul Kadir Kilian (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Tetanus Toxoid (TT) immunization is a way to actively generate/enhance a person's immunity against tetanus infection during or after childbirth. The coverage of TT immunization is still quite low, this is caused by various factors. Aim; determine the factors that influence the adherence to tetanus toxoid immunization of pregnant women. Method; quantitative method with a Cross-Sectional study approach using the shi-square test involving 130 samples. Sampling was done by purposive sampling technique using a questionnaire as a research instrument. Results; that mothers who comply with tetanus toxoid immunization are 74.6% while those who are not compliant are 25.4%. The results showed that there was a relationship between access (p = 0.000), attitude (p = 0.000), husband's support (p = 0.000), and the role of health workers (p = 0.016) with tetanus toxoid immunization compliance. There was no relationship between knowledge (p=0,285) and adherence to tetanus toxoid immunization. Conclusion; there is a relationship between access, attitude, husband's support, the role of health workers with tetanus toxoid immunization compliance.